PERLINDUNGAN HUKUM DALAM PERJANJIAN SEWA MENYEWA INDEKOS SECARA LISAN DAN NOTA BON PEMBAYARAN (STUDI KASUS RUMAH KOS DJOSARI) - M. Irfan; Ika Kartika (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the implementation of rental agreements and the legal protection provided to boarding house tenants, particularly in the context of oral agreements supported only by receipts. It also seeks to identify the challenges faced by tenants in such arrangements and the mechanisms available for resolving disputes and compensating losses. The research method employed in this thesis is empirical legal research, also known as sociological legal research or field research, which analyzes both the existing legal norms and their actual application in society. The findings reveal that lease agreements between boarding house owners and tenants are generally implemented in good faith; however, when disputes arise—particularly when one party suffers losses—the aggrieved party has the right to seek remedies such as specific performance, compensation for breach of contract, or even annulment of the agreement with restitution. Conflict resolution in cases of oral lease agreements is commonly conducted through non-litigation methods, particularly mediation or negotiation, reflecting the mutual intention of both parties to resolve issues amicably. Regarding oral lease agreements, termination by the lessor must follow customary practices by providing prior notice to the lessee. Furthermore, Articles 1709 and 1710 of the Indonesian Civil Code hold the landlord accountable for the loss of tenant belongings within the rented premises. However, specific legal regulations governing boarding house leases are not yet clearly defined in the Civil Code, highlighting the need for more tailored legal provisions.